2012
DOI: 10.1186/1757-7241-20-67
|View full text |Cite
|
Sign up to set email alerts
|

The Prehospital assessment of severe trauma patients` performed by the specialist ambulance nurse in Sweden – a phenomenographic study

Abstract: BackgroundA common feature of prehospital emergency care is the short and fragmentary patient encounters with increased demands for efficient and rapid treatment. Crucial decisions are often made and the premise is the specialist ambulance nurse’s ability to capture the situation instantaneously. The assessment is therefore a pre-requisite for decisions about appropriate actions. However, the low exposure to severe trauma cases in Sweden leads to vulnerability for the specialist ambulance nurse, which makes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 15 publications
2
50
0
9
Order By: Relevance
“…There are challenges for ambulance professionals associated with: (i) the assessment and triage of patients exposed to severe trauma and/or epilepsy seizures ; (ii) the referral of older people after falls ; (iii) religious and spiritual needs ; and (iv) differentiating frailty in older people . The extent of the challenges in emergency care situations was decisive for how decisions were made and demonstrated the challenges involved in getting to know individual patients .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are challenges for ambulance professionals associated with: (i) the assessment and triage of patients exposed to severe trauma and/or epilepsy seizures ; (ii) the referral of older people after falls ; (iii) religious and spiritual needs ; and (iv) differentiating frailty in older people . The extent of the challenges in emergency care situations was decisive for how decisions were made and demonstrated the challenges involved in getting to know individual patients .…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of severe trauma patients was perceived as a way of developing professional knowledge. More learning by practical skills training and feedback was needed , such as communication skills with dying patients and their families ; nursing critically ill and injured children ; and pain management . Lack of training in paediatrics was found to be a problem .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have underlined the importance of feedback from the management and acknowledgment for a job good made (36). This was also frequently wished for by responders in our study.…”
Section: Discussionmentioning
confidence: 72%
“…To educate for the uncommon situations when there are few assignments during the clinical rotation is a complex task. It was reported that the PECNs were sometimes worried about specific emergencies as well as situations related to the environment where the illness or injury occurred (Abelsson and Lindwall, 2012;Svensson and Fridlund, 2008). The lack of opportunities to practice may cause this worry.…”
Section: Discussionmentioning
confidence: 95%
“…Emergency situations that arise in the prehospital context require quick assessment and a fast response to increase the survival of patients (Bang et al, 2008), and there is little margin for error or misjudgement. Previous studies have found that the RNs working in the ambulance services are sometimes worried about specific emergencies as well as situations related to the environment where the illness or injury has occurred (Abelsson and Lindwall, 2012;Svensson and Fridlund, 2008). Developing expertise in the prehospital emergency care practice requires both theoretical and empirical learning.…”
Section: Introductionmentioning
confidence: 99%